(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To investigate the characteristics of colistin use and nephrotoxicity in patients with Klebsiella pneumoniae infections at Thong Nhat Hospital. Subject and method: This cross-sectional descriptive study was conducted on medical records of patients diagnosed with Klebsiella pneumoniae infections treated with colistin from January to June 2023 at Thong Nhat Hospital. Results: There were 54 medical records of patients infected with Klebsiella pneumoniae who were prescribed colistin and met the research criteria. The sensitivity of Klebsiella pneumoniae to various antibiotic groups was below 50%, except for a sensitivity of 73.0% to colistin and 63.6% to amikacin. All patients received colistin in combination regimens: dual (34.3%), triple (58.6%), and quadruple (7.1%), most commonly with carbapenem and an antibiotic active against Methicillin-resistant Staphylococcus aureus. A loading dose of colistin was administered to 47.2% of patients, with an average loading dose of 8.7 ± 1.1 million international units (MIU). The median maintenance daily dose was 6.8 MIU (interquartile range [IQR] 6.0-9.0), and the total cumulative dose was 45.0 MIU (IQR 27.0-65.3). Among the 43 cases evaluated for acute nephrotoxicity, 21 patients developed acute kidney injury, with 33.3% at risk, 23.8% injured, and 42.9% in failure according to the RIFLE criteria, with a median onset time of nephrotoxicity at 5.0 days (IQR 4.0-5.0). Conclusion: The incidence of acute kidney injury during colistin treatment for Klebsiella pneumoniae infections is high. Enhancing the closely monitoring renal function during treatment is crucial.